Clinicopathological features of follicular thyroid carcinoma coexisting with papillary thyroid carcinoma - Wang Hong-qun; Ma Ya-qi; Li Ying; Shi Huai-yin (Endocrine Journal)
To elucidate the clinicopathological features of follicular thyroid carcinoma (FTC) coexisting with papillary thyroid carcinoma (PTC) (FTC + PTC). We collected a total of 55 FTC + PTC patients (including 12 males [21.8%] and 43 females [78.2%]), with an average age of 47.6 years. In the FTC alone group, the average age was 52.3 years, and the proportion of females was 71.3%. The median age was 43.5 years, with an average age of 45 years in the PTC alone group. Compared with the tumors in the FTC alone group, FTC in the FTC + PTC group exhibited a smaller maximum diameter (49.1% measuring ≤2 cm), a younger patient age (70.9% younger than 55 years), an earlier tumor stage (94.5% in stages I–II), a lower incidence of recurrent cancer (n = 2, 3.6%), a lower frequency of distant metastasis (6.1%), and a lower proportion of “extensively invasive” subtype (12.7%) (all p < 0.05). Compared with the PTC alone group (n = 289), the FTC + PTC group had a higher proportion of PTC with a maximum diameter of ≤1 cm (72.5%), and the degree of invasion of thyroid extracellular tissue was less severe (all p < 0.05). No statistically significant differences were found in overall survival (OS), cancer-specific survival (CSS), and RFS between these two groups (the FTC or PTC alone group versus FTC + PTC group). In sum, FTC + PTC has some clinicopathological features.